Paleoeskimo Demography on Western Victoria Island, Arctic Canada: Implications for Social Organization and Longhouse Development - Savelle, James M.; Dyke, Arthur S.; Whitridge, Peter J.; Poupart, Melanie (ARCTIC, 2012)
Paleoeskimo populations on western Victoria Island reached maximum levels in Early Pre-Dorset time and declined abruptly shortly after 3800 14C years BP. The largest subsequent recovery occurred during Dorset time, particularly during Late Dorset, about 1500 to 600 BP. Early Pre-Dorset settlement patterns were similar to those documented for the same period and culture elsewhere in Arctic Canada, with dispersed nuclear families and small extended families occupying the region for most of the year, but with annual aggregations producing sites with 15 or more dwellings. After 3800 BP, large Pre-Dorset aggregation sites are absent. Dorset settlement patterns are dominated by multi-family longhouse – hearth row aggregation sites and by sites with two to four dwellings. Possibly the Dorset were living mainly in snow dwellings on the sea ice during cold seasons, with longhouses and hearth-row sets representing coming-ashore aggregations. Architectural aspects of longhouses and hearth rows indicate a common purpose behind their construction and use throughout the region and apparently throughout Arctic Canada, but their place and time of origin remain obscure. Radiocarbon dates place most longhouses and hearth rows on western Victoria Island in Late Dorset time, as elsewhere, but some dates indicate that these structures were being used in the western Canadian Arctic by Middle Dorset time. The latest Dorset radiocarbon dates from the region overlap with the earliest of the more reliable dates on Thule houses. Les populations paléoesquimaudes de l’ouest de l’île Victoria ont atteint leur summum à l’époque pré-Dorset puis ont chuté rapidement peu après 3800 années radiocarbones BP. Par la suite, la plus grande reprise s’est produite à l’époque du Dorset, plus particulièrement vers la fin de celui-ci, soit entre 1500 et 600 BP. Les types de peuplements du début du Dorset étaient semblables à ceux documentés pour la même période et pour la même culture ailleurs dans l’Arctique canadien, c’està- dire qu’il y avait des ...